Evaluation of Wear Mechanisms in Sucker Rod Pumps Under Varying Load and Lubrication Conditions - Khalig Mammadov; Tahir Suleymanov; Suleyman Efendi (Tribology in Industry, 2025)
The durability and efficiency of sucker rod pumps (SRPs) in oil and gas extraction are significantly affected by wear and fatigue phenomena, particularly under high-load and extreme environmental conditions. This study examines the tribological behavior of SRP materials through pin-on-disk wear testing, assessing the impact of load variations, lubrication types, and material composition on specific wear rate and coefficient of friction (CoF). Experiments were conducted on AISI 4140 alloy steel, tungsten carbide-coated rods, and polymer-based materials, subjected to dry, crude oil-based, and synthetic nano-additive lubrication conditions. The findings indicate that higher loads generally exacerbate wear and friction, with dry contact conditions producing the highest CoF (0.68) and specific wear rate (7.4×10-3 mm3/Nm). Nano-additive lubrication proved most effective, reducing CoF to 0.26 and specific wear rate to 2.1×10-3 mm3/Nm. Among the tested materials, tungsten carbide coatings exhibited the greatest durability with a minimum specific wear rate of 1.3×10-3 mm3/Nm, while polymer-based materials demonstrated the highest specific wear rate of 8.5×10-3 mm³/Nm under high load. Microstructural analysis via SEM and EDS revealed plastic deformation, fatigue-induced cracking, and material transfer, particularly under 1500 N load. ANOVA analysis confirmed that lubrication type and material composition had a statistically significant influence on wear behavior (p < 0.05), while load variations had limited effect. These results emphasize the importance of material and lubrication optimization in enhancing SRP performance.